Polymeric biomaterials in the treatment of posterior segment diseases - Seah, Ivan; Ong, Charles; Liu, Zengping; Su, Xinyi (Frontiers in Medicine, 2022)
Polymeric biomaterials are biological or synthetic substances which can be engineered to interact with biological systems for the diagnosis or treatment of diseases. These biomaterials have immense potential for treating eyes diseases, particularly the retina - a site of many inherited and acquired diseases. Polymeric biomaterials can be engineered to function as both as an endotamponade agent and to prevent intraocular scarring in retinal detachment repair surgeries. They can also be designed as a drug delivery platform for treatment of retinal diseases. Finally, they can be used as scaffolds for cellular products and provide non-viral gene delivery solutions to the retina. This perspective article explains the role of polymeric biomaterials in the treatment of retinal conditions by highlighting recent advances being translated to clinical practice. The article will also identify potential hurdles to clinical translation as future research directions in the field.